Exploring Metal Electroplating for Energy Storage by Quartz Crystal Microbalance : A Review - Vanoppen, Viktor; Johannsmann, Diethelm; Hou, Xu ; 0000-0003-0398-2006; Sjölund, Jens; Broqvist, Peter; Berg, Erik J. (Advanced Sensor Research, 2024)
The development and application of Electrochemical Quartz Crystal Microbalance (EQCM) sensing to study metal electroplating, especially for energy storage purposes, are reviewed. The roles of EQCM in describing electrode/electrolyte interface dynamics, such as the electric double-layer build-up, ionic/molecular adsorption, metal nucleation, and growth, are addressed. Modeling of the QCM sensor is introduced and its importance is emphasized. Challenges of metal electrode use, including side reactions and dendrite formation, along with their mitigation strategies are reviewed. Numerous factors affecting the electroplating processes, such as electrolyte composition, additives, temperature, and current density, and their influence on the electroplated metals’ mass, structural, and mechanical characteristics are discussed. Looking forward, the need for deeper fundamental understanding and advancing simulations of the QCM signal response as a result of electroplating metal nanostructures is stressed. Further development and integration of innovative EQCM-strategies will provide unique future means to fundamentally understand and optimize metal electroplating for energy storage and application alike.
Publisher Copyright: © 2024 The Authors. Advanced Sensor Research published by Wiley-VCH GmbH.
Keywords: batteries; energy storage; metal electroplating; modeling; quartz crystal microbalance